Internalisasi Nilai-Nilai Keislaman dalam Pembentukan Karakter: Analisis Integratif Muhaimin-Lickona di Sekolah Dasar Negeri Indonesia - Miyarsi Miyarsi; Nuni Oktaviani (Fakultas Pendidikan IAI Pangeran Dharma Indramayu, 2026)
Character education in the digital disruption era requires approaches that transcend cognitive knowledge transfer. This study aims to analyze the role of educators in internalizing Islamic values for character formation in public elementary schools and to test the relevance of Muhaimin’s internalization model in the context of children's cognitive development. Employing a qualitative case study approach, data were collected through participant observation, in-depth interviews, and documentation at UPTD SDN 1 Haurgeulis, Indonesia (January–June 2025). Participants were selected via purposive sampling (1 principal, 5 teachers, 6 students, 4 parents). Data analysis utilized the interactive model of Miles, Huberman, and Saldaña. The findings reveal that exemplary behavior (uswah) and religious habituation serve as epistemological bridges connecting the abstract understanding of Islamic values with students' concrete moral actions. Integrating Muhaimin’s value internalization theory (transformation, transaction, transinternalization) with Lickona’s character education dimensions (moral knowing, feeling, action) produces a comprehensive framework explaining how religious values transform into character dispositions. Theoretically, this study revises Muhaimin’s transinternalization concept by incorporating concrete habituation variables to accommodate Piaget’s concrete operational stage in elementary students. Practically, public elementary schools must restructure school culture into a moral ecosystem involving a tripartite synergy (school, family, community) to counter the negative impacts of digital culture.